Genome-wide comparison and in silico analysis of splicing factor SYF2/NTC31/p29 in eukaryotes: Special focus on vertebrates - Huang, Bao-Xing; Jia, Zi-Chang; Yang, Xue; Cheng, Chao-Lin; Liu, Xiao-Rong; Zhang, Jianhua; Chen, Mo-Xian; Yang, Jing-Fang; Chen, Yun-Sheng (Frontiers in Genetics, 2022)
SYF2 (RNA splicing factor) can interact with cyclin D-type binding protein 1 (GICP) to participate in many biological processes, such as splicing regulation, cell cycle regulation and DNA damage repair. Our previous study performed genome-wide identification and functional analysis of SYF2 in plant species. However, the phylogenetic relationships and expression profiles of SYF2 in animals have not been systematically studied. To this end, the gene structure, genes, and protein conserved motifs of 102 SYF2 homologous genes from 91 different animal species were systematically analysed, and conserved splicing sites in 45 representative vertebrate species were analysed. A differential comparative analysis of expression patterns was performed between humans and mice. Molecular bioinformatics analysis of SYF2 showed that it was conserved and functional in different animal species. In addition, expression pattern analysis found that SYF2 was specifically highly expressed in hematopoietic stem cells, T cells, lymphoid progenitor cells, ovary, lung, spleen and other cells or organs. This suggests that changes in SYF2 expression may be associated with disease development in these cells, tissues or organs. In conclusion, our study analysed the SYF2 disease resistance genes of different animal species through bioinformatics, revealed the relationship between SYF2 genotype and the occurrence of certain diseases, and provided a theoretical basis for the follow-up study of the relationship between the SYF2 gene and animal diseases.